2011
DOI: 10.1002/lary.22145
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation has a positive influence on quality of life, tinnitus, and psychological comorbidity

Abstract: The present study provides evidence that tinnitus and psychological comorbidity may play an important role in the rehabilitation of CI patients, and that there is a correlation between HRQoL and these parameters. In addition to hearing tests, tinnitus, stress, and psychological comorbidity should be assessed using validated questionnaires before and after CI. This will help to improve the rehabilitation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
138
4
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(168 citation statements)
references
References 21 publications
(11 reference statements)
11
138
4
7
Order By: Relevance
“…The version of the NCIQ translated into Brazilian Portuguese showed good internal consistency (Cronbach's α coefficient of 0.78), corroborating the data described in the literature (8,18) . Thus, as observed in previous studies, the results of this research showed that, after one year and five months of CI activation and regardless of gender, there was a positive effect on the users' QoL for all domains evaluated: physical, social, and psychological (8,21,22) . The overall score obtained in the group of individuals evaluated by the NCIQ-P version (70.25) was close to the data reported by other authors, (74.2) and (63.26), and described in the scientific literature (18,22) .…”
Section: Resultssupporting
confidence: 87%
“…The version of the NCIQ translated into Brazilian Portuguese showed good internal consistency (Cronbach's α coefficient of 0.78), corroborating the data described in the literature (8,18) . Thus, as observed in previous studies, the results of this research showed that, after one year and five months of CI activation and regardless of gender, there was a positive effect on the users' QoL for all domains evaluated: physical, social, and psychological (8,21,22) . The overall score obtained in the group of individuals evaluated by the NCIQ-P version (70.25) was close to the data reported by other authors, (74.2) and (63.26), and described in the scientific literature (18,22) .…”
Section: Resultssupporting
confidence: 87%
“…Overall, implanted adults showed significant improvement in QoL after implantation [Chung et al, 2012;Hawthorne et al, 2004;Klop et al, 2007Klop et al, , 2008Mo et al, 2005;Olze et al, 2011;Zhao et al, 2008] and attained significantly higher QoL than their nonimplanted (hearing-aided) peers [Cohen et al, 2004;Looi et al, 2011]. There were no differences in QoL between implanted adults and normal-hearing peers [Rembar et al, 2012].…”
Section: Summary Of Findings For Adultsmentioning
confidence: 98%
“…These include the Nijmegen Cochlear Implant Questionnaire (NCIQ) [Cohen et al, 2004;Damen et al, 2007;Fuller et al, 2013;Klop et al, 2007;Looi et al, 2011;Olze et al, 2011 ], the Cochlear Implant Function Index (CIFI) [Fuller et al, 2013], the Speech, Spatial and Qualities Questionnaire (SSQ) [Fuller et al, 2013], Patient Quality of Life Form (PQLF) [Mo et al, 2005], Index Relative Questionnaire Form (IRQF) [Mo et al, 2005], the Hearing Participation Scale (HPS) [Hawthorne et al, 2004], and the Complete Intelligibility Spatiality Quality (CISQ) [Looi et al, 2011].…”
Section: Disease-specific Instruments In Adultsmentioning
confidence: 99%
“…The present results suggest that CI users may experience a relief in tinnitus persistence, but not a complete abolition of tinnitus or tinnitus-related distress. Studies investigating other aspects of tinnitus handicap in CI users are encouraging (e.g., anxiety and depression; Andersson et al 2009;Olze et al 2011;Kloostra et al 2015), but a more comprehensive characterization of tinnitus symptoms is still needed to understand the burden of tinnitus after cochlear implantation. It is only through such understanding that appropriate interventions for alleviating the burden of tinnitus in implant users can be identified and developed.…”
Section: Discussionmentioning
confidence: 99%